Personal Health Records Mobile App - Leong, Xian Jun (2020)
Due to the increased population, the data size of the health records can become tremendous. Eventually, it can hardly be handled by humans. Therefore, technology shall take over human manpower in handling and tracking health records. With this, this project developed a system that aids the patients in keeping track their health records while helping the medical staff in handling the health records. Beside health record tracking, the product of this project aimed to provide extra services such as appointment scheduling and medication reminder. Phased development methodology was chosen and implemented in this project. Thus, this project consists of four phases, which are the planning phase, analysis and design phase, development and testing phase as well as the closing phase. Background of the problem was studied in the planning phase. During the analysis and design phase, the project requirements were finalized and system architecture and designs were modelled. In the development and testing phase, it was further separated into three sub-phases, which each sub-phase focused on modules with different priority levels. After completion of the development, the system was tested for its usability and 83 scores were given for the satisfaction of the applications. With the completion of this project, the patients could use the mobile application to keep track of their health records while the medical staff can manage the health records via the web application. Despite there are more for improvement, this project is considered a great success as it fulfils all of the defined objectives.